Molecular characterization of Rice ragged stunt virus and Rice grassy stunt virus on Rice in Gianyar, Bali, Indonesia - Yuliadhi, Ketut Ayu; Listihani, Listihani; Selangga, Dewa Gede Wiryangga; Yuniti, I Gusti Ayu Diah; Ariati, Putu Eka Pasmidi (Universitas Lampung, 2024)
Rice stunt disease is one of the causes of rice harvest failure. It is caused by the infection of Rice ragged stunt virus (RRSV) and Rice grassy stunt virus (RGSV) infection. Information about disease severity and the molecular characteristics of stunt viruses in Indonesia is still limited. Thus, this research aimed to determine the disease severity and the genetic diversity of rice stunt viruses in Gianyar, Bali. The research method consisted of observation of incidence and disease severity in the field and virus detection by reverse transcription-polymerase chain reaction (RT-PCR) using primers specific for RRSV and RGSV. The observation of the disease incidence and severity were performed in seven districts in Gianyar Regency, Bali, namely Blahbatuh, Gianyar, Payangan, Sukawati, Tampaksiring, Tegallalang, and Ubud. Stunt disease was found in all observation sites. High stunt disease incidence (> 44%) was found in three districts: Ubud, Tampaksiring, and Payangan, while the low disease incidence rate of <10% was found in Blahbatuh and Gianyar Districts. The highest stunt disease severity occurred in Tampaksiring District (60.82%), while the lowest severity occurred in Gianyar District (18.84%). The IR-64 and Ciherang cultivars are vulnerable to rice stunt disease infection. The highest homology of RRSV and RRGV nucleotides was found with Vietnam isolates being >98% and >97%, respectively. The phylogenetic analysis showed that Indonesian isolates of RRSV and RGSV were clustered in the same group as Vietnam isolates.